2020
DOI: 10.1016/j.landusepol.2020.104553
|View full text |Cite
|
Sign up to set email alerts
|

Understanding farmers’ climate adaptation intention in Iran: A protection-motivation extended model

Abstract: Adaptation to climate change is a matter of urgent social scientific analysis. Within the agricultural sector of many developing nations, farmers must make long-term decisions to adapt to climate change impacts in order to provide food security and sustainable livelihoods.However, deeper understanding of farmers' decision-making, as a key stakeholder group, is of vital importance in forming adaptive land use policy 'from the bottom-up'. This study investigates the psychosocial factors that influence farmers' a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 105 publications
2
34
0
3
Order By: Relevance
“…The relationship between BI and WCB of farmers has been studied extensively [4,6,12,13,21,24,36,38,42,44]. Intention may be related to some water-saving behaviors that include the use of methods or tools that reduce water consumption, cultivation of water saving crops or modified seeds, performing activities with low water consumption [27,45], the use of drought-and-salinity-resistant or less water-demanding varieties, less tillage, or a combination of such technologies and practices [46]. Haghi et al [47] have showed that BI influences membership behavior in the WUCs.…”
Section: Hypothesis 4 (H4)-behavioral Intention and Wcbmentioning
confidence: 99%
“…The relationship between BI and WCB of farmers has been studied extensively [4,6,12,13,21,24,36,38,42,44]. Intention may be related to some water-saving behaviors that include the use of methods or tools that reduce water consumption, cultivation of water saving crops or modified seeds, performing activities with low water consumption [27,45], the use of drought-and-salinity-resistant or less water-demanding varieties, less tillage, or a combination of such technologies and practices [46]. Haghi et al [47] have showed that BI influences membership behavior in the WUCs.…”
Section: Hypothesis 4 (H4)-behavioral Intention and Wcbmentioning
confidence: 99%
“…The second challenge is the lack of balance in the daily diet, and environmental degradation is the third challenge [ 24 ]. Food insecurity is a great barrier facing welfare and development and it can make human future uncertain and vague [ 9 , 14 , 21 , 25 , 35 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mazandaran is isolated between the Caspian Sea in the north and the Alborz mountains in the south, which will be influenced by the humid weather (caused by sea) and cold weather (coming from the mountains). For this reason, the climate in this province is mostly moderate and subtropical with an average temperature of 25 • C and 8 • C in summer and winter, respectively [57], which finally decreases significantly the total drought hazard and risk (90.48).…”
Section: Discussionmentioning
confidence: 99%